Solve for x
x=\frac{36000-7y}{11}
Solve for y
y=\frac{36000-11x}{7}
Graph
Share
Copied to clipboard
0.035y+0.055x+82.5=262.5
Use the distributive property to multiply 0.055 by x+1500.
0.055x+82.5=262.5-0.035y
Subtract 0.035y from both sides.
0.055x=262.5-0.035y-82.5
Subtract 82.5 from both sides.
0.055x=180-0.035y
Subtract 82.5 from 262.5 to get 180.
0.055x=-\frac{7y}{200}+180
The equation is in standard form.
\frac{0.055x}{0.055}=\frac{-\frac{7y}{200}+180}{0.055}
Divide both sides of the equation by 0.055, which is the same as multiplying both sides by the reciprocal of the fraction.
x=\frac{-\frac{7y}{200}+180}{0.055}
Dividing by 0.055 undoes the multiplication by 0.055.
x=\frac{36000-7y}{11}
Divide 180-\frac{7y}{200} by 0.055 by multiplying 180-\frac{7y}{200} by the reciprocal of 0.055.
0.035y+0.055x+82.5=262.5
Use the distributive property to multiply 0.055 by x+1500.
0.035y+82.5=262.5-0.055x
Subtract 0.055x from both sides.
0.035y=262.5-0.055x-82.5
Subtract 82.5 from both sides.
0.035y=180-0.055x
Subtract 82.5 from 262.5 to get 180.
0.035y=-\frac{11x}{200}+180
The equation is in standard form.
\frac{0.035y}{0.035}=\frac{-\frac{11x}{200}+180}{0.035}
Divide both sides of the equation by 0.035, which is the same as multiplying both sides by the reciprocal of the fraction.
y=\frac{-\frac{11x}{200}+180}{0.035}
Dividing by 0.035 undoes the multiplication by 0.035.
y=\frac{36000-11x}{7}
Divide 180-\frac{11x}{200} by 0.035 by multiplying 180-\frac{11x}{200} by the reciprocal of 0.035.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}